TAREKAT DAN MODERASI BERAGAMA - Feriyanto Feriyanto (Balai Diklat Keagamaan Bandung, 2020)
Tarekat Qadariyah Naqsabandiyah (TQN) is the research’s subject, due to the phenomenon of religious moderation among TQN practitioners. The research uses phenomenological method. The data are collected through participant observation, interviews, and literature review. Data analysis techniques are completed by reducing, presenting, and concluding. The results show that the practices; first, religious moderation’s form exists among practitioners of inclusive TQN and social solidarity. Second, internalized teachings of tanbih values are involving moderate attitude in religion, social protection, calm and peace in life. Third, tanbih teachings changes for the better and shows attitudes ranging from intolerance to tolerance, narrow thinking to wisdom and broadness, mutual respect, moderation in religion and among the practitioners even when they have different backgrounds. The role of “Guru Murshid” is the most important facet in maintaining religious moderation. Keyword: religious moderation; religious experience; tanbih; tarekat